2022
DOI: 10.1155/2022/3278943
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Root Canal Anatomy of Mandibular Permanent Incisors in Saudi Subpopulation: A Cone-Beam Computed Tomography (CBCT) Study

Abstract: This study aimed to evaluate the root canal anatomy of central and lateral mandibular incisors in a Saudi population using cone-beam computed tomography (CBCT). Overall, 1370 CBCT images of central (687) and lateral (683) mandibular incisors of Saudi patients who attended the Dental College at King Saud University in Riyadh were examined. The number of roots and canals, canal configuration types, symmetry between bilateral incisors, and the effect of gender and age were determined. For data analysis, the chi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Meanwhile, Al-Fouzan et al, [ 23 ] utilizing staining and clearing techniques, observed that about one-third of the Riyadh population had 2 canals in their mandibular incisors. Mohamed et al [ 24 ] reported that a single root with 2 root canals was the most common root canal configuration in the mandibular incisors of a Saudi subpopulation in the Qassim region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, Al-Fouzan et al, [ 23 ] utilizing staining and clearing techniques, observed that about one-third of the Riyadh population had 2 canals in their mandibular incisors. Mohamed et al [ 24 ] reported that a single root with 2 root canals was the most common root canal configuration in the mandibular incisors of a Saudi subpopulation in the Qassim region.…”
Section: Discussionmentioning
confidence: 99%
“…Some examples are improving the nickel-titanium (NiTi) rotary and reciprocating the instrument, using ultrasonic equipment for effective disinfection, and using different obturation techniques, such as continuous wave and hydraulic obturation (single cone with hydraulic silicate cements). [ 24 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Po ashtu, grupet e dhëmbëve mund të kenë variacione anatomike me incidencë të ndryshme. Shumica e incizivëve mandibularë kanë një rrënjë të vetme me një kanal [6], mirëpo konfigurimi i kanalit të rrënjës në incizivët mandibularë mund të jetë i komplikuar me praninë e variacioneve anatomike, si kanali i dytë i rrënjës, kanali lateral i rrënjës dhe delta apikale [7]. Studimet kanë treguar se prevalenca e dy kanaleve në incizivët mandibularë sillet prej 11-70% [8][9][10][11].…”
Section: Hyrjeunclassified